Amyloid-β precursor protein modulates the sorting of testican-1 and contributes to its accumulation in brain tissue and cerebrospinal fluid from patients with Alzheimer disease (2016)
The mechanisms leading to amyloid-β (Aβ) accumulation in sporadic Alzheimer disease (AD) are unknown but both increased production or impaired clearance likely contribute to aggregation. To understand the potential roles of the extracellular matrix proteoglycan Testican-1 in the pathophysiology of AD, we used samples from AD patients and controls and an in vitro approach. Protein expression analysis showed increased levels of Testican-1 in frontal and temporal cortex of AD patients; histological analysis showed that Testican-1 accumulates and co-aggregates with Aβ plaques in the frontal, temporal and entorhinal cortices of AD patients. Proteomic analysis identified 10 fragments of Testican-1 in cerebrospinal fluid (CSF) from AD patients. HEK293T cells expressing human wild type or mutant Aβ precursor protein (APP) were transfected with Testican-1. The co-expression of both proteins modified the sorting of Testican-1 into the endocytic pathway leading to its transient accumulation in Golgi, which seemed to affect APP processing, as indicated by reduced Aβ40 and Aβ42 levels in APP mutant cells. In conclusion, patient data reflect a clearance impairment that may favor Aβ accumulation in AD brains and our in vitro model supports the notion that the interaction between APP and Testican-1 may be a key step in the production and aggregation of Aβ species. © 2016 Oxford University Press OR American Association of Neuropathologists.